2020
DOI: 10.1038/s41525-020-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

MutSpot: detection of non-coding mutation hotspots in cancer genomes

Abstract: Recurrence and clustering of somatic mutations (hotspots) in cancer genomes may indicate positive selection and involvement in tumorigenesis. MutSpot performs genome-wide inference of mutation hotspots in non-coding and regulatory DNA of cancer genomes. MutSpot performs feature selection across hundreds of epigenetic and sequence features followed by estimation of position-and patient-specific background somatic mutation probabilities. MutSpot is user-friendly, works on a standard workstation, and scales to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…For further comparison, we ran four existing and available methods [DriverPower ( 27 ), Larva ( 28 ), MutSpot ( 29 ), and OncodriveFML ( 5 )] on the entire WGS dataset. This revealed that our genome-wide approach identified nearly all the noncoding events detected by these four methods in the genomic territory included in our analysis (figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further comparison, we ran four existing and available methods [DriverPower ( 27 ), Larva ( 28 ), MutSpot ( 29 ), and OncodriveFML ( 5 )] on the entire WGS dataset. This revealed that our genome-wide approach identified nearly all the noncoding events detected by these four methods in the genomic territory included in our analysis (figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the biological function of genomic positions, other factors, including nucleotide contexts, coverage fluctuation, read mappability, and kataegis events, affect positional clustering. Concepts similar to those of test 3 have been used in other methods for analyzing coding and noncoding regions ( 9 , 29 ). Therefore, test 3 examines whether mutations occur in different positions than expected by chance, but it does not analyze whether the total number of mutations deviates from the expectation and thus does not require calibration against regional fluctuations of the background mutation rates.…”
Section: Materials and Methods Summarymentioning
confidence: 99%
“…Application of maxATAC to the growing number of genetic studies with population-level and single-cell ATAC-seq will improve the power of these studies to accurately predict TF mediators of allelic chromatin accessibility and gene expression. Furthermore, many genetic tools use overlap with TFBS to nominate potentially causal risk variants [58][59][60], where TFBS are predicted based on suboptimal TF motif scanning or ChIP-seq in a potentially suboptimal cell type or condition, due to lack of data in the in vivo disease context. Integration of maxATAC TFBS predictions into genetic analysis pipelines will be the focus of future work.…”
Section: Maxatac Performance Extends To Primary Cellsmentioning
confidence: 99%
“…For instance, highly recurrent mutations in the promoter region of TERT gene have been found in more than 50 tumor types, prompting efforts to identify additional non-coding driver events [134,135]. However, there are at present few computational tools specifically tailored for detecting drivers in non-coding regions (e.g., [82,89,136]). Identifying signals of positive selection in non-coding DNA is even more challenging because the non-coding region is about 50 times larger than the coding exome, and the number of known cancer genes with noncoding mutations is much more limited [134,137].…”
Section: Non-coding Driversmentioning
confidence: 99%